A Cold Active Bifunctional Lipase with Protease Activity from Antarctic Microorganism Pi 12 - Mohamad Ali, Mohd Shukuri (2009)
A psychrophilic microorganism (cold loving) named PI 12 was isolated from the Antarctic sea ice near Casey station, Antarctica. This psychrophilic microorganism produced extracellular lipase and the activity was determined by using both qualitative and quantitative methods. Clearing zones was formed when it was grown at 4°C on top of tributyrin agar plates, indicating an extracellular cold active lipase with activity at 0.051U/ml. 16rRNA genes revealed an apparent homology of 99 % to Janthibacterium sp. However, further identification of isolate PI 12 confirmed that it was a yeast, Leucosporodium antarcticum. The lipase gene of isolate PI 12 was isolated via shotgun cloning. Gene analysis showed an open reading frame of 783 bp was found to encode a lipase. The lipase was assayed at 4ºC with activity at 0.1 U/ml. The gene was also successfully expressed extracellularly by co-transformation of pJL3 plasmid which encode Bacteriocin Release Protein (BRP) The lipase gene did not show high similarity to other lipases as anticipated. Interestingly, the gene shared high homology to protease. Thus more investigations in trying to understand such novel finding were done. In order to visualize the enzyme, LipPI12 was modeled using the template of psychrophilic protease from Pseudomonas sp. TACII18. The putative 3D structure of the enzyme showed the typical properties of psychrophilic enzyme, which is increasing number of loops and a non compact structure to cater the lipase structural flexibility. Purification of recombinant intracellular and extracellular LipPI12 was done using Nickel Sepharose affinity chromatography. The purified intracellular LipPI12 was a monomer with the size of ~30kDa as judge native and SDS PAGE respectively. LipPI12 holds huge prospect of greater finding therefore characterization of LipPI12 lipase and protease were done. Temperature profile of the bifunctional LipPI12 showed that the lipase functions optimally at 20°C and reached half life after 30 min whereas the protease was more active at 40°C but reaches half life even faster after 15 mins of incubation. pH profile showed that both LipPI12 lipase and protease were active at near neutral condition. Medium chain length fatty acid (C12) seemed to be the best substrate for LipPI12 lipase. The presence of organic solvents did not affect both the lipase and protease activities. The lipase was more stable at solvents with higher log P value whereas the protease was slightly activated at low log P value particularly with dimethylsulfonyl. Activity of LipPI12 lipase and protease were also activated in the presence of CaCl2 but its protease counterpart seemed to be more active in the presence of other metal ions such as ZnCl2 and MgCl2. Effect of surfactants showed LipPI12 lipase was activated by Tween 80 and SLS and in contrast, LipPI12 protease was almost deactivated in all surfactants tested. Inhibitor studies revealed that LipPI12 lipase was partially inhibited with EDTA and PMSF whereby the LipPI12 protease was inhibited by pepstatin and was also partially inhibited by EDTA and PMSF. Amino acid comparison showed patterns of cold adaptation with increasing number of glycine and lesser proline. Circular dichroism and fluorescence spectroscopy analysis, strengthens the findings which entails protein psychrophilicity. The findings of unique LipPI12 has led to better understanding of the enzyme as shown from its bifunctional properties. The contrasting figure of LipPI12 lipase and protease reveals greater elucidation on protein structure and function. Thus it is concluded that LipPI12 lipase and protease is a remarkable enzyme which has highlighted way of surviving the cold and also promises potential application in the future.